Trends in resource utilization and cost of illness in patients with active epilepsy in Germany from 2003 to 2020 - Willems, Laurent M.; Hochbaum, Maja; Zöllner, Johann Philipp; Schulz, Juliane; Menzler, Katja; Langenbruch, Lisa; Kovac, Stjepana; Knake, Susanne; von Podewils, Felix; Hamacher, Mario; Hamer, Hajo; Reese, Jens Peter; et al. (Epilepsia, 2022)
Objective: This study was undertaken to calculate epilepsy-related direct, indirect, and total costs in adult patients with active epilepsy (ongoing unprovoked seizures) in Germany and to analyze cost components and dynamics compared to previous studies from 2003, 2008, and 2013. This analysis was part of the Epi2020 study. Methods: Direct and indirect costs related to epilepsy were calculated with a multicenter survey using an established and validated questionnaire with a bottom-up design and human capital approach over a 3-month period in late 2020. Epilepsy-specific costs in the German health care sector from 2003, 2008, and 2013 were corrected for inflation to allow for a valid comparison. Results: Data on the disease-specific costs for 253 patients in 2020 were analyzed. The mean total costs were calculated at €5551 (±€5805, median = €2611, range = €274–€21 667) per 3 months, comprising mean direct costs of €1861 (±€1905, median = €1276, range = €327–€13 158) and mean indirect costs of €3690 (±€5298, median = €0, range = €0–€11 925). The main direct cost components were hospitalization (42.4%), antiseizure medication (42.2%), and outpatient care (6.2%). Productivity losses due to early retirement (53.6%), part-time work or unemployment (30.8%), and seizure-related off-days (15.6%) were the main reasons for indirect costs. However, compared to 2013, there was no significant increase of direct costs (−10.0%), and indirect costs significantly increased (p <.028, +35.1%), resulting in a significant increase in total epilepsy-related costs (p <.047, +20.2%). Compared to the 2013 study population, a significant increase of cost of illness could be observed (p =.047). Significance: The present study shows that disease-related costs in adult patients with active epilepsy increased from 2013 to 2020. As direct costs have remained constant, this increase is attributable to an increase in indirect costs. These findings highlight the impact of productivity loss caused by early retirement, unemployment, working time reduction, and seizure-related days off.
CRIS-Team Scopus Importer:2022-04-15
Keywords: antiseizure medication; cost of illness; economic burden; health care; seizure